Relationality as the Hidden Side of the Apophatic William of Saint-Thierry's Appreciation and Critique of XIIth Century Apophaticism. Issue 1 (2nd January 2016) - Faesen, Rob
Abstract : Recent contributions to the study of mysticism often treat the apophatic dimension of mystical language. This focus is inspired by contemporary continental thinkers such as Jacques Derrida or Jean-Luc Marion. William of Saint-Thierry (1075–1148) sets out his own interpretation of the apophatic dimension of mysticism in a short passage in his On the Nature and Dignity of Love — in reaction to, among others, Peter Abaelard. William considers reason's negating activity, which puts aside all that is not God, as progress towards God because it entails a rejection of everything that may appear to be or purport to be God. However, the inner certainly of it, according to William, is due to the active presence of an Other in the human movement towards God — which, thus, is both active and passive. William's underlying fundamentally relational and 'open' anthropology is developed later by Hadewijch and John of Ruusbroec.